EXAMINING THE SIGNIFICANCE OF EFFECTIVELY MANAGING MEETINGS IN AN ORGANISATION - SHONHIWA, DOCTOR CAXTON (IJRDO- Journal of Educational Research, 2017)
This paper examines the significance of effectively managing meetings in the context of a school. In order to keep track of the work progress, regular meetings can be conducted where team members share each other’s development. The whole team is constantly updated with how well the project goes and what things need to be worked on. Another example is when there are changes in the school goals. The manager may call for a meeting to discuss the changes with the members so they are updated with any modifications. On the part of the management, conducting a meeting makes it easy for them to deliver any important updates at one time and at the same time to the members. Meetings also provide an opportunity for the management to acknowledge the accomplishments of group members through public recognition. Meetings also help group members to reach a common decision when urgent and crucial matters need to be discussed and brainstormed through personal interaction. Individuals must understand that meetings are very essential to the success of the organization. Although a meeting is an integral part of office routine and some may find it plain and boring in the long run, meetings go beyond achieving goals; they foster and strengthen good working relationships as well.